Ionospheric effects in the Southern radiation anomaly - Torr, Douglas G (Rhodes University, Faculty of Science, Department of Physics, 1966)
From introduction: As ionosphericist on the 4th South African National Antarctic Expedition, I spent twelve months at Sanae (70°18'S, 2°2l'W, L= 4) in 1963. In the course of routine vertical incidence soundings, it was noticed with some surprise that the frequency of occurrence of ionospheric blackouts was unexpectedly high. Initially this aroused considerable concern about the reliability of the equipment. In fact it has been · observed that some stations lying in and near the Southern Radiation Anomaly report such occasions as records lost due to non-ionospheric reasons. Coincidently, however, Gledhill and van Rooyen (1963), also of Rhodes University, predicted ionospheric irregularities and other geophysical phenomena in a region around Sanae where Ginsburg et al. (1962) observed high intensities of charged particles with Sputniks 5 and 6.
Keywords: Uncatalogued